Direct observations of asteroid interior and regolith structure: Science measurement requirements. Issue 8 (15th October 2018) - Herique, A.; Agnus, B.; Asphaug, E.; Barucci, A.; Beck, P.; Bellerose, J.; Biele, J.; Bonal, L.; Bousquet, P.; Bruzzone, L.; Buck, C.; Carnelli, I.; et al.
Abstract: Our knowledge of the internal structure of asteroids is, so far, indirect – relying entirely on inferences from remote sensing observations of the surface, and theoretical modeling of formation and evolution. What are the bulk properties of the regolith and deep interior? And what are the physical processes that shape asteroid internal structures? Is the composition and size distribution observed on the surface representative of the bulk? These questions are crucial to understand small bodies' history from accretion in the early Solar System to the present, and direct measurements are needed to answer these questions for the benefit of science as well as for planetary defense or exploration. Radar is one of the main instruments capable of sounding asteroids to characterize internal structure from sub-meter to global scale. In this paper, we review the science case for direct observation of the deep internal structure and regolith of a rocky asteroid of kilometer size or smaller. We establish the requirements and model dielectric properties of asteroids to outline a possible instrument suite, and highlight the capabilities of radar instrumentation to achieve these observations. We then review the expected science return including secondary objectives contributing to the determination of the gravitational field, the shape model, and the dynamical state. This work is largely inherited from MarcoPolo-R and AIDA/AIM studies.